2004
DOI: 10.1097/01.pas.0000126859.70814.6d
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis in Lymphangioleiomyomatosis

Abstract: Lymphangioleiomyomatosis (LAM) is characterized by the proliferation of abnormal smooth muscle cells (LAM cells) in the lungs, lymph nodes, and/or other organs. We examined lymphangiogenesis using immunohistochemistry for Flt-4 (VEGFR-3), a new specific marker for lymphatic endothelial cells, as well as the expression of vascular endothelial growth factor (VEGF)-C in LAM. Specimens were obtained from 6 autopsy cases, a single lung transplant case, and 8 surgical cases for analyses. We demonstrated that lymphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(50 citation statements)
references
References 28 publications
0
49
0
1
Order By: Relevance
“…Slit-like channels, lined with lymphatic endothelial cells, traverse LAM foci or nodules in lung and extrapulmonary LAM-affected organs ( i.e . lymph node, uterus and ovaries) [23, 24] and appear to be lymphatic capillaries.…”
Section: Lymphangioleiomyomatosismentioning
confidence: 99%
See 2 more Smart Citations
“…Slit-like channels, lined with lymphatic endothelial cells, traverse LAM foci or nodules in lung and extrapulmonary LAM-affected organs ( i.e . lymph node, uterus and ovaries) [23, 24] and appear to be lymphatic capillaries.…”
Section: Lymphangioleiomyomatosismentioning
confidence: 99%
“…Immunohistochemical studies involving TSC neoplasms (kidney AMLs, cortical tumours and skin lesions) reported the expression and up-regulation of the angiogenic growth factor vascular endothelial growth factor (VEGF)-A [41, 42] and the vascular endothelial marker CD31 [41]. In contrast, evidence of angiogenesis (positive staining for CD31) was observed less in LAM lung foci [23], and serum levels of VEGF-A in LAM patients were no different from those of controls [43]. Collectively, data from these experiments suggest angiogenesis as a partial mechanism for pathogenesis of TSC.…”
Section: Lymphangioleiomyomatosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, only 40% of patients with LAM have uterine leiomyomas [1]. Other putative sources of LAM cells are renal AML, axial lymphatics [67], and perivascular epithelioid cell tumors [66]. …”
Section: Lam and Tuberous Sclerosismentioning
confidence: 99%
“…LAM cells express the lymphangiogenic factors VEGF-C and VEGF-D and their receptors VEGFR-2 and VEGFR-3 [67]. In TSC2-deficient cells in vitro, VEGF secretion is markedly elevated and this effect is only partly reverted by sirolimus, suggesting that tuberin regulates VEGF through both mTOR-dependent and mTOR-independent pathways [76].…”
Section: Lam and Tuberous Sclerosismentioning
confidence: 99%